2021
DOI: 10.1038/s41598-021-96337-0
|View full text |Cite
|
Sign up to set email alerts
|

A national assessment of elective cesarean sections in Bangladesh and the need for health literacy and accessibility

Abstract: There has been a gradual rise in the number of cesarean sections (CSs) in Bangladesh. The present study identified the cohort of women, who were more likely to opt for an elective CS based on their sociodemographic characteristics, pre-delivery care history, and media exposure, using the Bangladesh Multiple Indicator Cluster Survey-2019. The survey stratification adjusted logistic regression model and interpretable machine learning method of building classification trees were utilized to analyze a sample of 92… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…However, consistent with the present study, recent evidence from Bangladesh has shown that residing in urban areas has no association with c-Sects. [52]. The emerging health literacy about the procedures of c-section deliveries in Bangladesh might explain this.…”
Section: Discussionmentioning
confidence: 99%
“…However, consistent with the present study, recent evidence from Bangladesh has shown that residing in urban areas has no association with c-Sects. [52]. The emerging health literacy about the procedures of c-section deliveries in Bangladesh might explain this.…”
Section: Discussionmentioning
confidence: 99%
“…Choosing the mode of delivery appears to be influenced by health literacy. A study in Bangladesh showed that health awareness, health education, and better health communication via mass media foster mothers' ability to access appropriate health care advice on options for a safe birth and other related issues [22].…”
Section: Discussionmentioning
confidence: 99%
“…Ahmed, Khoja and Tirmizi [ 26 ] reported that strict religious norms hinder mothers’ access to antenatal care. Furthermore, male dominance in a factor in societies such as Bangladesh and Pakistan, which may have played a role in care for mothers and seeking appropriate medical services [ 27 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%